2017
DOI: 10.1097/nmd.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Preferences Regarding Antidepressant Medication Among Depressed Latino Patients in Primary Care

Abstract: US Latinos are less likely to utilize mental health services than non-Latino Whites, and to take antidepressant medication. This mixed-method study followed a subset (N=28) of a research sample of depressed Latino immigrant primary care patients with a telephone interview to study their knowledge about and experiences with antidepressant medications. Most (82%) reported taking medication for two months or more, and 75% reported feeling better, while over half reported side effects. Most (61%) agreed that antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…The combined effects of stigma, discrimination, and the therapeutic alliance (including patient–provider communication) may be more responsible for differences in access and continued engagement in mental health treatment, rather than a set of fixed treatment preferences or beliefs based on race and ethnicity. For example, one study found that most Hispanic/Latino patients with depression in primary care (61%) thought antidepressants were safe and helpful, but a large portion (39%) feared they could be addictive, and half of them did not tell their provider when they stopped their medication treatment (Green et al, 2017). Other studies point to the value that psychiatric patients deposit on shared decision-making as a cornerstone of quality care (Thomas et al, 2018) and the role of therapists as worthy “co-pilots” to increase engagement in depression treatment (Heilemann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of stigma, discrimination, and the therapeutic alliance (including patient–provider communication) may be more responsible for differences in access and continued engagement in mental health treatment, rather than a set of fixed treatment preferences or beliefs based on race and ethnicity. For example, one study found that most Hispanic/Latino patients with depression in primary care (61%) thought antidepressants were safe and helpful, but a large portion (39%) feared they could be addictive, and half of them did not tell their provider when they stopped their medication treatment (Green et al, 2017). Other studies point to the value that psychiatric patients deposit on shared decision-making as a cornerstone of quality care (Thomas et al, 2018) and the role of therapists as worthy “co-pilots” to increase engagement in depression treatment (Heilemann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the selected studies used various data sources; the majority obtained from patients (n=21), and direct methods were not used in the included studies. As previously mentioned the variation of the prevalence of medication adherence, the rate of adherence as assessed by using self-reported, claims database/refill data, pill count, health provider's report (self-report, patient record) ranged from 10.6% to 81%, 19,[21][22][23]34,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] 10% to 62.9%, 25,34,63-70 45%, 71,72 and 69.2% to 85.4%, 34,58 respectively. The most common included studies utilized standardized and structured data collection tool, and structured interviews to measure adherence.…”
Section: Methods To Assess Medication Adherencementioning
confidence: 99%
“…Also, patient occupation in service and farming reported a significantly high adherence rate than business, housewife, and students. 60 Lack of family support and the nature of the job stated the reasons for nonadherence. 57,65 Studies conducted in different contexts reported that lack of support from family members, spouses, and friends was found barriers from delayed initiating AD medication and continuing it.…”
Section: Factors Affect To Medication Adherencementioning
confidence: 99%
“…Adolescents are more likely to seek health care if their provider assures con dentiality, but in providing con dential care a balance should be considered between the needs of the adolescent patient, parents, and provider [54]. In literature, distrust towards psycho-therapist is most commonly reported as barrier to therapy engagement in Latino adult populations [48,[55][56][57][58][59][60][61][62].…”
Section: Con Dentialitymentioning
confidence: 99%